Physical capital investments and labour productivity across countries-Panel approach. - Trpeski, Predrag; Cvetanoska, Marijana; Kozheski, Kristijan (Varazdin Development and Entrepreneurship Agency, Varazdin, Croatia / University North, Koprivnica, Croatia / Faculty of Management University of Warsaw, Warsaw, Poland / Faculty of Law, Economics and Social Sciences Sale -Mohammed V University in Rabat, Morocco / Polytechnic of Medimurje in Cakovec, Cakovec, Croatia, 2019)
It is recognized that gross capital formation has a direct, but also anindirectimpact on the labour productivity.Physical capital naturally has an important role for the economic growth and labour productivity. It has always been seen as potential determinant for enhancing productivity growth.Based on an intensive and a comprehensive literature review, the aim of the paperis to analyze the extent of correlation and causal relationship between gross fixed capital formation and labour productivity on different group of countries for the period 2004 –2016. The countries which are subject of the analysis are divided into three groups based on the geographical location and their economic and structural performance. In order to examine the correlation between the gross fixed capital formation and labour productivity, it is used an uncentered correlation coefficient. Foranalyzing the casual relationship between variables inlcuded in this study, an econometric panel regression analysis of the three groups of countries is employed. Therefore, an attempt is made for an econometric analysis based on panel data. The results of the correlation analysis show a positive correlation in the individual groups of countries analyzed in this study. It pointed out that the degree of correlation differs between the individual panel analysis. Moreover, such a conclusion can be drawn basedon the results obtained from the regression panel analysis. That is, the causal relationship in individual country groups is statistically significant and positive. On the other hand, on average the different coefficients of the β coefficients indicate a different degree of causality between the gross fixed capital formation as an independent variable and the labour productivity as the dependent variable in the different groups of countries. The strength of the causal relationship is quite different given the economic, structural and other characteristics of separate group of countries.
Keywords: gross fixed capital formation, labour productivity, panel data, physical capital investments